Rancang Bangun Alat Pendeteksi Kendaraan Dari Arah Berlawanan Pada Tikungan Tajam Berbasis Arduino UNO - Ayuni Finda Rika; Nuzul Hikmah (Jurnal JEETech, 2021)
A sharp bend is a bend that has an acute angle with the level of difficulty when the vehicle crosses the road. In sharp turns frequent vehicle accidents occur. Accidents are caused by vehicles traveling at high speeds when they will cross the bend in the road. In addition, the driver also wants to overtake the vehicle when going through the bend. By making this warning system, it is expected to reduce accidents on the road bends. This tool can detect the presence of a vehicle and will give a warning in the form of an indicator light that is controlled by the Arduino UNO microcontroller using an Ultrasonic sensor and will light up if within 10 m before crossing the road bend there is a vehicle that will pass